Voluntary urination control by brainstem neurons that relax the urethral sphincter. (September 2018) - Keller, Jason; Chen, Jingyi; Simpson, Sierra; Wang, Eric; Lilascharoen, Varoth; George, Olivier; Lim, Byung; Stowers, Lisa
Abstract Voluntary urination ensures that waste is eliminated when safe and socially appropriate, even without a pressing urge. Uncontrolled urination, or incontinence, is a common problem with few treatment options. Normal urine release requires a small region in the brainstem known as Barrington's nucleus (Bar), but specific neurons that relax the urethral sphincter and enable urine flow are unknown. Here we identify a small subset of Bar neurons that control the urethral sphincter in mice. These excitatory neurons express estrogen receptor 1 (BarESR1 ), project to sphincter-relaxing interneurons in the spinal cord and are active during natural urination. Optogenetic stimulation of BarESR1 neurons rapidly initiates sphincter bursting and efficient voiding in anesthetized and behaving animals. Conversely, optogenetic and chemogenetic inhibition reveals their necessity in motivated urination behavior. The identification of these cells provides an expanded model for the control of urination and its dysfunction. Controlling urination is a fundamental social need. Keller et al. develop a voluntary urination assay and uncover a subset of brainstem neurons that relax the urethral sphincter, providing insight into urinary control and its dysfunction.